Why Do Some Find it Hard to Disagree? An fMRI Study - Domínguez D, Juan F.; Taing, Sreyneth A.; Molenberghs, Pascal (Frontiers in Human Neuroscience, 2016)
People often find it hard to disagree with others, but how this disposition varies across individuals or how it is influenced by social factors like other people’s level of expertise remains little understood. Using functional magnetic resonance imaging (fMRI), we found that activity across a network of brain areas (comprising posterior medial frontal cortex, anterior insula, inferior frontal gyrus, lateral orbitofrontal cortex, and angular gyrus) was modulated by individual differences in the frequency with which participants actively disagreed with statements made by others. Specifically, participants who disagreed less frequently exhibited greater brain activation in these areas when they actually disagreed. Given the role of this network in cognitive dissonance, our results suggest that some participants had more trouble disagreeing due to a heightened cognitive dissonance response. Contrary to expectation, the level of expertise (high or low) had no effect on behavior or brain activity.